Economic values and factors influencing management and conservation attributes of Kubah National Park, Sarawak, Malaysia - Abu Bakar, Nor Afiza (2016)
Protection and conservation of environmental resources in most countries around the world rely heavily on the presence of national parks and protected areas. These areas offer highly beneficial use and non-use values for both current and future generation. Nevertheless, it is extremely difficult to express these economic values in monetary terms as typically there are regarded as nonmarketable values. Ecotourism activities in national parks are one of the significant contributors to the growth of tourism industry, but often it comes at a price. Thus, sustainable management and conservation of national parks require understanding of public and park visitors’ attitude and preferences. The general objective is to assess the visitors and non-visitors’ preferences and economic values of Kubah National Park (KNP). In order to realize the aims of the study, Contingent Valuation Method (CVM) and Choice Modeling (CM) method were utilized. A total of 618 respondents involved in face-to-face interviews, which involved a stratified random sampling selected for data collection. In the CVM method, a dichotomous choice CVM (DC-CVM) was employed to derive the respondents’ WTP for improvement in management and conservation aspects at KNP. The logit models were used to elicit their WTP for the proposed price bids. Results from the study evidenced that in both samples, as the price bids increases, the probability of saying ‘Yes’ decreases. The estimated mean for the WTP is an increment of 71.74% (RM7.17 for Malaysian and RM14.35 for foreigner) for the visitor’s sample and 53.10% for the nonvisitor’s sample (RM5.31), above the current entrance fee charges (RM10 for Malaysian and RM20 for foreign visitors). In the CM method, Choice Experiment (CE) was employed by using conditional logit (CLGT) models to investigate the respondent’s preferences of the management and conservation attributes. The estimations were split into two parts: Part A for Ecotourism and Management attributes (EMT) and Part B covers for National Park and Conservation attributes (NPC). CLGT models were applied in order to capture the marginal values of these chosen attributes. The study finds that visitors have positive WTP for all EMT and NPC attributes. Nonvisitors also have positive WTP for all attributes except for Natural Attractions (NA) in its EMT attributes. Marginal rate substitution was estimated to find out the WTP for each single of the EMT and NPC attributes. The results show that for EMT attributes, both samples are concerned with information availability the most and in the NPC attributes, there are more willing to pay more for fauna and flora observation as well as enforcement level. Findings of the study may assist national parks’ manager and policy makers in evaluating current entrance fee charges as well as in designing strategic management and conservation policies for sustainable ecotourism development in Kubah National Park and other national parks in Sarawak.